Acute effects of non‐weathered and weathered crude oil and dispersant associated with the Deepwater Horizon incident on the development of marine bivalve and echinoderm larvae. (27th May 2016) - Stefansson, Emily S.; Langdon, Chris J.; Pargee, Suzanne M.; Blunt, Susanna M.; Gage, Susan J.; Stubblefield, William A.
Abstract: Acute toxicity tests (48–96‐h duration) were conducted with larvae of 2 echinoderm species ( Strongylocentrotus purpuratus and Dendraster excentricus ) and 4 bivalve mollusk species ( Crassostrea virginica, Crassostrea gigas, Mytilus galloprovincialis, and Mercenaria mercenaria ). Developing larvae were exposed to water‐accommodated fractions (WAFs) and chemically enhanced water‐accommodated fractions (CEWAFs) of fresh and weathered oils collected from the Gulf of Mexico during the Deepwater Horizon incident. The WAFs (oils alone), CEWAFs (oils plus Corexit 9500A dispersant), and WAFs of Corexit alone were prepared using low‐energy mixing. The WAFs of weathered oils had no effect on survival and development of echinoderm and bivalve larvae, whereas WAFs of fresh oils showed adverse effects on larval development. Similar toxicities were observed for weathered oil CEWAFs and WAFs prepared with Corexit alone for oyster ( C. gigas and C. virginica ) larvae, which were the most sensitive of the tested invertebrate species to Corexit. Mean 10% effective concentration values for total polycyclic aromatic hydrocarbons and dipropylene glycol n‐butyl ether (a marker for Corexit) in the present study were higher than all concentrations reported in nearshore field samples collected during and after the Deepwater Horizon incident. The results suggest that water‐soluble fractions of weathered oils and Corexit dispersant associated with the Deepwater Horizon incident had limited, if any, acute impacts on nearshore larvae of eastern oysters and clams, as well as other organisms with similar sensitivities to those of test species in the present study; however, exposure to sediments and long‐term effects were not evaluated. Environ Toxicol Chem 2016;35:2016–2028. © 2016 SETAC